An Analysis of Students’ Ability on Writing Skills in Recount Text at Tenth Grade of SMAN 9 Kota Jambi - Dini Andriani; Wennyta Wennyta (JELT: Journal of English Language Teaching, 2020)
The purpose of this research is to analyze the students’ ability on writing skills in recount text at tenth grade of SMA N 9 Kota Jambi. This research used descriptive research with qualitative method. This research used random sampling to get the sample and then got X MIS 3 as a sample with the total 36 students but two students did not follow the test. So that, there were 34 students as a sample. In collecting the data, the instrument of this research is writing test by using recount text.The findings of this research showed that, the student’s ability on writing skill in recount text was categorized 5 students or (15%) were categorized excellent, 20 students or (59%) were categorized good, and 9 students or (26%) were categorized satisfactory,there were no students who get categorized unsatisfactory and failed. Then, the researcher get the result from analysis students ability on writing skills in recount text that is Good in writing skills especially in aspect content or generating ideas. The researcher can conclude that students are understand more about content aspect or generating ideas on writing skills but most of students are still confused and difficult in other aspect.Key Words: Students’ Ability, Recount Text.